Answer:
y = x - 2
Step-by-step explanation:
y = mx + b
5 = 1 (7) + b
5 = 7 + b
b = -2
So...
y = x - 2
Answer:
5.4217 • 10¹
Step-by-step explanation:
4.5 • 10⁻² ÷ 8.3 • 10⁻⁴
450 ÷ 8.3
54.21686...
54.217
5.4217 • 10¹
I hope this helps
Answer:
No Solutions.
Step-by-step explanation:
I will solve your system by substitution.
3y−3=3x; −3x+3y=−57
Step: Solve 3y−3=3x for y:
3y−3+3=3x+3 (Add 3 to both sides)
3y=3x+3
(3y/3=3x+3)/3
(Divide both sides by 3)
y=x+1
Step: Substitute x+1 for y in −3x+3y=−57:
−3x+3y=−57
−3x+3(x+1)=−57
3=−57 (Simplify both sides of the equation)
3+(−3)=−57+(−3) (Add -3 to both sides)
0=−60
Answer:
C
Step-by-step explanation: